Frequency of physical therapy in knee osteoarthritis: a randomized controlled trial - Murat, Sadiye; Yumuşakhuylu, Yasemin; Gençoğlu, Zeliha; İçağasıoğlu, Afitap; Kesiktaş, Nur; Altınbilek, Turgay (The European Research Journal, 2019)
Objectives: This study is conducted to compare the three different frequency of the physical therapy application for knee osteoarthritis in female patients.Methods: Consecutive 89 female patients with knee osteoarthritis were randomized into three groups of physical therapy as twice-daily, once-a-day and alternate day, by computerized random number generator. We used Visual Analog Scale (VAS); to determine pain level, Western Ontario McMaster Osteoarthritis Index (WOMAC); to determine osteoarthritis (OA) severity, 10-meter walking test (WD); to determine walking speed and Short Form (SF-36) questionnaire; to determine the quality of life. All groups received a total of 10 physical therapy sessions including hot pack, therapeutic ultrasound (US) and transcutaneous electrical nerve stimulation (TENS). We evaluated subjects at the beginning, at the end of treatment and at the third month control at post-treatment period.Results: Improvement was observed in all groups after treatment (p < 0.05). While there was no significant difference in once-a-day treatment group at 3rd month control (p > 0.05), alternate day group showed a significant improvement (p < 0.05). Conclusions: In the treatment of knee osteoarthritis, usually once-a-day physical therapy approach is preferred in daily practice. Alternatively twice a day or alternate day therapies can be applicable.